U-Pb ages of detrital zircons from the Internal Betics: A key to deciphering paleogeographic provenance and tectono-stratigraphic evolution - Jabaloy-Sánchez, A.; Talavera, Cristina; Gómez-Pugnaire, M.; López-Sánchez-Vizcaíno, V.; Vázquez-Vílchez, M.; Rodríguez-Peces, M.; Evans, Noreen (Elsevier BV, 2018)
© 2018 Elsevier B.V. Zircons from the Nevado-Filábride Complex metamorphic rocks yielded 891 concordant inherited detrital ages. The 342 concordant ages from the Aulago Fm indicate a Pennsylvanian maximum depositional age, while the age density distribution indicates that this formation is closely related to the Cantabrian Zone (north of the Iberian Massif). The dominant Ediacaran and Cryogenian populations, at ca. 596 and 788 Ma respectively, relate the Nevado-Filábride Complex to northern Gondwana terranes. A discrete Mesoproterozoic zircon population at ca. 1031 Ma (Tonian-Late Estenian population) suggests that the basement of the Nevado-Filábride Complex could have been located near of the Saharan Metacraton and west of the East African Orogen at the beginning of the Paleozoic. The 549 concordant ages from the Tahal Fm yield an Early Permian age for the protoliths. The age density distribution pattern records erosion of rocks from the Variscan belt, including Late-Variscan magmatic rocks. Zircon spectra differ from those of the Alborán Domain, supporting the hypothesis that the Nevado-Filábride Complex is part of the South Iberian Domain. Furthermore, data from the Tahal Fm are similar to those of Permo-Triassic rocks from the Iberian Ranges.